Harold Ancart - traveling light - McLean-Ferris, Laura 1982- (David Zwirner Books, 2021)
Ancart often paints subjects that naturally invite contemplation, such as the horizon, clouds, flowers, flames, and icebergs. His newest body of work captures the experience of landscape seen in motion or from a distance: trees blurred while driving past, a far-off inky-black sea, an evocative Martian mountain range. Recalling René Magritte, Egon Schiele, Gustav Klimt, and Piet Mondrian, who approached this subject matter in distinct ways, Ancart blurs form and color, figure and ground, and figuration and abstraction.00Reproduced here in magnificent foldouts, two multipanel canvases situate the viewer between a mountainscape and a seascape, both monumental in scale. Ancart segments the seascape with a stark horizon line, dividing sky and ocean. Like other comparable motifs within the artist?s oeuvre, the vividly colored cloudy sky functions in an anthropomorphic way, alluding to the endless possibilities and personalities of organic forms.00Including an interview with the artist by Bob Nickas, this catalogue offers insight into Ancart?s frank reflections on painting, writing, nature, and more. The publication also features a new essay by Laura McLean-Ferris. Taken together, the works in Traveling Light meditate on the expansive possibilities of painting.00Exhibition: David Zwirner Gallery, New York, USA (10.09.-17.10.2020)
Impressum: Published by David Zwirner Books on the occasion of "Harold Ancart: Traveling Light", David Zwirner, New York, September 10 - October 17, 2020
Keywords: Ancart, Harold -- 1980-; Ancart, Harold / 1980-; Ausstellungskatalog -- Gallery David Zwirner -- 10.09.2020-17.10.2020 -- New York, NY; Bildband